432 RENAL AND SYSTEMIC RESPONSES TO NITRIC OXIDE BLOCKADE IN GP91PHOX KNOCKOUT MICE. (1st January 2005) - Haque, M. Z.; Castillo, A.; Majid, D. S.A.
Abstract : An interactive role of nitric oxide (NO) and superoxide (O2-) in the regulation of renal function has been suggested in recent studies. NAD(P)H oxidase is known to be a major source of O2- production in the kidney. To understand further this NO-O2- interaction in the kidney, we have assessed the renal responses to systemic administration of NO synthase inhibitor, nitro-L-arginine methyl ester (L-NAME; 0.2 μg/min/g BW) in inactin anesthetized knockout (KO, n = 8) mice, deficient of gene for gp91phox and compared these responses to that in wild-type (WT, C57BL/6, n = 7) mice. Renal blood flow (RBF) and glomerular filtration rate (GFR) were measured by PAH and inulin clearances respectively. Baseline mean arterial blood pressure (BP) recorded from a carotid arterial cannula was not different between KO (91 ± 4 mm Hg) and WT mice (92 ± 6 mm Hg). Basal RBF was higher in KO compared to WT (5.4 ± 0.5 vs. 4.3 ± 0.3 mL.min-1.g-1, p < .05). However, basal levels of renal vascular resistance (RVR, 18.5 ± 2.5 and 22.2 ± 1.8 mm Hg.mL-1.min-1.g-1), GFR (0.56 ± 0.06 and 0.64 ± 0.06 mL.min-1.g-1), urine flow (V, 6.9 ± 1.5 and 9.5 ± 2.2 μL.min-1.g-1) and sodium excretion (UNaV, 0.67 ± 0.1 and 0.84 ± 0.3 μmoL.min-1.g-1) were not significantly different between KO and WT mice respectively. In WT mice, L-NAME infusion for 60 minutes resulted in a reduction of 17 ± 4 % in RBF and an increase of 55 ± 9% in RVR. Interestingly, L-NAME caused less reduction in RBF (10 ± 3%) and less increases in RVR 34 ± 6% in KO mice compared to WT. There were no changes in GFR during L-NAME infusion in both the KO (0.56 ± 0.06 mL.min-1.g-1) and in WT (0.69 ± 0.08 mL.min-1.g-1) mice. Systemic infusion of L-NAME also caused increases in BP (109 ± 5 and 115 ± 4 mm Hg), V (21 ± 4 and 30 ± 5 μL.min-1.g-1) and UNaV (4.0 ± 0.8 and 5.5 ± 1.0 μmoL.min-1.g-1) in KO and WT mice respectively. Although the excretory responses to L-NAME were generally lower in KO mice compared to WT mice, but these changes were not significantly different. L-NAME increased urinary excretion of 8-isoprostane in WT (4.7 ± 0.7 to 8.7 ± 1.2 pg/min/g, p < .05) but not in KO mice (4.8 ± 0.6 to 5 ± 0.4 pg/min/g) indicating increased O2- activity in WT mice during NO blockade. These data further support the notion that renal responses to NO blockade are influenced by enhancement of O2- activity induced by NAD(P)H oxidase.